Online Launch of the Participatory Climate Information Services for Agriculture Manual - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
This is the edited version of the Participatory Integrated Climate Services for Agriculture (PICSA) webinar held late October. Download presentation from the seminar: http://ow.ly/U2ERG Learn more about PICSA: https://ccafs.cgiar.org/PICSA